Adjusting for Design Effects in Disproportionate Stratified Sampling Designs Through Weighting. - Tracy, Paul E.; Carkin, Danielle Marie (Crime & Delinquency, 2014)
This article validates the necessity of adjusting for the design effects in disproportionate stratified sampling designs through the use of sample weights. Using data from the 1958 Birth Cohort study, we demonstrate that complex sampling designs introduce sampling error and even sampling bias into sample data. Such sample data are a poor representation of population parameters. These design effects can be addressed through the application of sample weights.